2019
DOI: 10.1038/s41598-019-48160-x
|View full text |Cite
|
Sign up to set email alerts
|

An integrated transcriptomic analysis of autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is not a single disease but a set of disorders. To find clues of ASD pathogenesis in transcriptomic data, we performed an integrated transcriptomic analysis of ASD. After screening based on several standards in Gene Expression Omnibus (GEO) database, we obtained 11 series of transcriptomic data of different human tissues of ASD patients and healthy controls. Multidimensional scaling analysis revealed that datasets from the same tissue had bigger similarity than from different tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Is it realistic to study the xy interaction independent from the triadic interconnection (xyz) it lives in? Specially in case of heterogeneous brain disorders such as ASD, a complex neurodevelopmental disorder with substantial heterogeneity not only in multiple causes and courses but also in the onset [8][9][10][11] . Recently, this concern has been well addressed by the long-standing structural balance theory (SBT) in variety of scenarios, and triadic interactions are accepted to play…”
mentioning
confidence: 99%
“…Is it realistic to study the xy interaction independent from the triadic interconnection (xyz) it lives in? Specially in case of heterogeneous brain disorders such as ASD, a complex neurodevelopmental disorder with substantial heterogeneity not only in multiple causes and courses but also in the onset [8][9][10][11] . Recently, this concern has been well addressed by the long-standing structural balance theory (SBT) in variety of scenarios, and triadic interactions are accepted to play…”
mentioning
confidence: 99%
“…Interestingly, two of the main hubs, HERC4 and TMEM30A, were included in immune system pathways. These findings suggested that core ASD co-predictors are linked to responses of the immune system and its signal can be detected in blood, as it has been reported earlier (Enstrom et al, 2009;He et al, 2019). To examine nonlinear and linear associations, we compared the most highly ranked co-predictors to the co-expression profiles.…”
Section: Discussionmentioning
confidence: 58%
“…It has been shown that the gene expression profile of NK cells was altered in peripheral blood of children with ASD (Enstrom et al, 2009). Another transcriptomics data analysis of ASD subjects demonstrated similarities in functional enrichment between brain and blood (He et al, 2019). The study revealed significant enrichment in terms of immune response, mitochondrion-related functions, and oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 88%
“…Next-Generation Sequencing (NGS) technology has gifted biomedical science a tool for exploration of big data, especially for complex diseases like ASD. While there have been several rigorous efforts to explore the transcriptome of ASD [7][8][9][10][11][12][13][14], there has been a limited exploration of the proteome of ASD [15][16][17][18][19]. Little has been done to understand the proteome, let alone characterize the functional effectors of the phosphoproteome in syndromic ASD contexts, such as those arising from Mendelian gene variation, here, germline PTEN mutation.…”
Section: Discussionmentioning
confidence: 99%